An Absolutely Chilean Institution. Línea Aérea Nacional, Chile (1929–45) - Barria-Traverso, D (SAGE Publications Inc., 2019)
This article analyses the early Chilean State experience in the management of its flagcarrying airline, Línea Aérea Nacional. Drawing on Línea Aérea Nacional documents as well as newspapers, laws, and parliamentary debates, the article reconstructs the development of the company between 1929 and 1945. The central argument of this article is that, although Línea Aérea Nacional was created as an instrumental State-owned enterprise to ensure national sovereignty, the airline lived through three stages, each one of them dependent on the economic policy priorities of the different governments. The first stage started with Línea Aérea Nacional’s initial activities; the second stage covers the period 1932–40 and was characterised by a financial and operational crisis. During the third stage (1941 onwards) a scheme of long-lasting State financing was granted. It allowed Línea Aérea Nacional to renew its fleet, expand – nationally and internationally – its routes, and improve its financial and operational outcomes. © The Author(s) 2019.